Collaborative of Guardians in the Early Intervention Program of Pre-School Hearing Students at The Special Education School - Abdul Manap Seriman; Mohd Hanafi Mohd Yasin (Journal of ICSAR, 2021)
Collaboration is the most important aspect for special students, especially those with deaf and hard of hearing (DHH). This study was conducted aimed to explore the understanding and collaborative effectiveness of early intervention of DHH peoples from the guardians perspective. The design of this study uses a fully qualitative case study in the Johor Bahru Special Education School (JBSES). The interview method was used to obtain data involving three guardians pre-school students at JBSES. The theory used in this study is Bronfrenbrenner’s Theory of Ecology. The model used is the Bronfrenbrenner ecological social model. The findings of the study indicate the extent of the effectiveness of collaboration in early intervention for DHH students where parents are understanding and participated in all activites in the school. Most of the parents contributed to the school activities. Other than that there is support from Non Governments Organisation (NGOs) and the outside parties to the school.